2021
DOI: 10.4018/978-1-7998-3343-7.ch004
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Oasis Agriculture to Climate Change in Morocco

Abstract: Morocco is considered one of the most threatened countries by climate change. Over the last century, oases ecosystems in this country showed a high vulnerability to climate variation, which has led to water scarcity, an increase in land salinity, and therefore, a decrease in agricultural production. Conscious of these issues, several solutions are initiated by the government to cope with climate change adverse effects. Many programs of rehabilitation were launched, and advanced researches are in progress in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…The functional profile of the microbial communities might be correlated with changes in community composition at the species level, suggesting that 'suitability phenomena' between the host plant and its native microbial communities, rather than a "generalistic" inoculum, may be functionally driven rather than driven by phylogeny 70 . Previous studies reported the effectiveness of native inoculum, which promotes and maintains plant growth despite the low colonization percentages under abiotic stresses 22,26,57 . Essahibi et al 72 reported that long-term drought stress decrease root colonization in carob seedlings inoculated with Rhizophagus intraradices, R. fasciculatus and Funneliformis mosseae.…”
Section: Discussionmentioning
confidence: 99%
“…The functional profile of the microbial communities might be correlated with changes in community composition at the species level, suggesting that 'suitability phenomena' between the host plant and its native microbial communities, rather than a "generalistic" inoculum, may be functionally driven rather than driven by phylogeny 70 . Previous studies reported the effectiveness of native inoculum, which promotes and maintains plant growth despite the low colonization percentages under abiotic stresses 22,26,57 . Essahibi et al 72 reported that long-term drought stress decrease root colonization in carob seedlings inoculated with Rhizophagus intraradices, R. fasciculatus and Funneliformis mosseae.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several decades, the management of sustainable ecosystems has been an arising interest in both academia and industry Ait El Mokhtar et al (2021), Cinner et al (2022), Maulu et al (2021), Mohanty et al (2010), Rahman et al (2022). Typical topics include the impacts of climate change on various ecosystems including aquaculture.…”
Section: Introductionmentioning
confidence: 99%
“…This is a target that emanated from the 21st Conference of Parties (COP21) where the Paris Agreement was enacted in 2015. The adverse consequences of climate change on various economic sectors have already been felt by many nations and every fraction of temperature increase results in loss of life or livelihood, the agricultural sector being the most hard-hit [4][5][6][7][8]. The major problem is that evidence has shown that improving the environment while expanding the economy cannot coexist.…”
Section: Introductionmentioning
confidence: 99%